Sustainable Culinary Tourism in Ubud, Bali: Preserving Traditional Balinese Food Heritage while Supporting Tourism Growth - Suardani, Made; Meirejeki, I Nyoman; Sagitarini, Luh Linna; Sudarta, I Gede; Arjana, I Wayan Basi (PT Keberlanjutan Strategis Indonesia, 2026)
Sustainable tourism has increasingly emphasized the importance of balancing economic development with cultural preservation. Within this framework, culinary tourism has emerged as a strategic tool for enhancing destination attractiveness while maintaining local identity. This study aims to examine the role of sustainable culinary tourism in preserving traditional Balinese food heritage while supporting tourism growth in Ubud, Bali. A qualitative case study approach was employed, involving in-depth interviews with restaurant owners, local chefs, cooking class instructors, and tourism practitioners, complemented by observations and document analysis. The findings reveal that sustainable culinary tourism contributes significantly to the preservation of traditional recipes, cooking techniques, and the use of local ingredients. Culinary tourism activities, particularly traditional restaurants and cooking classes, function as mechanisms for transmitting culinary knowledge and strengthening cultural authenticity. Furthermore, culinary tourism enhances destination competitiveness, increases tourist attraction, and supports local economic development. Local community involvement was identified as a critical factor in ensuring sustainability, as community members serve as custodians of traditional culinary knowledge. However, challenges related to commercialization and adaptation to tourist preferences may threaten authenticity if not properly managed. This study concludes that sustainable culinary tourism provides an integrated model for balancing cultural preservation and tourism growth. The findings contribute to sustainable tourism and culinary tourism literature by demonstrating the dual role of culinary tourism in cultural sustainability and economic development. Practical implications are provided for policymakers, tourism practitioners, and local communities to strengthen sustainable culinary tourism strategies in cultural destinations.